DISNEY’S SEXIST LANGUAGE: FEMINIST STYLISTIC APPROACH IN BEAUTY AND THE BEAST (2017) - Romadhon, Sahrul (RADIANT: Journal of Applied, Social, and Education Studies, 2020)
Through the feminist stylistic on Walt Disney’s Beauty and the Beast (2017) Live-Action remake, the paper argues that Walt Disney is not as inclusive and progressive as rumoured, but sexist. The study aims to uncover the characteristics of sexism in the context of linguistic derived from a gender-specific term. This study is qualitative research. The objects and data of this analysis are determined by purposive sampling. The object of this study is the text that appeared in the film Beauty and the Beast (2017) on a live-action remake. The data for this study are lexical items (single word, chain of words, and part of a word) that relate to gender-specific. The data analysed using the linguistic determinism theory of Sara Mill's feminist stylistic framework. This study reveals the presence of sexism at the word level. The findings are Walt Disney’s Beauty and the Beast (2017) Live-action remake shows the use of generic-noun and generic-pronouns appear in a sexist way, diminutive naming of gay and female characters, and negative terms used to portray female characters.